Teknologi Bioflok untuk Ikan Rawa - Abror, Muhammad; Tiawati, Evi; Manurung, Cindi N; Khairunnisa, Mutiara; Saptaviana Susilo, Tasya; Vivin, Vivin (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2022)
Abror M, Tiawati E, Manurung CN, Khairunnisa M, Susilo TS, Vivin V. 2022. Biofloc technology for swamp fish. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-10 Tahun 2022, Palembang 27 Oktober 2022. pp. 621-627. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Swamp fish cultivation is currently a special attraction for fish farmers, but its production is still not optimally utilized, it can be increased by using a biofloc system. The biofloc system is a technology that utilizes bacteria that are able to destroy waste and maintain water quality with the advantage of being able to maximize narrow land, environmentally friendly, feed efficiency and high productivity. Therefore, the use of a biofloc system for swamp fish farming is very helpful for farmers because they can get increased yields from a limited pond area and save on feed costs. So the cultivation technology using a biofloc system is highly recommended to be developed in swamp fish farming. This study aimed to study the effect of the biofloc system on the productivity of swamp fish farming production. This activity is carried out by looking at and comparing several related scientific journals and then getting the best knowledge for the biofloc system in swamp fish.